VOLUME PERDAGANGAN, FREKUENSI PERDAGANGAN, ORDER IMBALANCE DAN VOLATILITAS HARGA SAHAM - Agustinus Agustinus (Universitas Paramadina, 2013)
AbstractStock price volatility reflects the risk dan opportunity gained by investors. Investors need to pay attention on indicators in technical analysis that will affect stock prices volatility, such as trading volume, trading frequency, and the absolute difference between demand volume and supply volume, known as order imbalance. This study is aimed at examining the effect of trading volume, trading frequency, and order imbalance on stock price volatility.The population of the study is all public firms listed at Indonesian Stock Exchange for periods of 2009-2010. Sample is determined using purposive sampling where the selected sample firms are not those conducting stock split, stock dividend, and right issue during the study periods.The results show that trading volume and order imbalance do not affect stock price volatility, whilst trading frequency affect negatively stock price volatility. The coefficient for trading frequency is in the opposite direction as it is expected to have positive sign.Keywords: trading volume, order imbalance, trading frequency, stock price volatility.